Tenascin-C suppresses Rho activation. - Wenk, M; Midwood, K; Schwarzbauer, J (2000)
Cell binding to extracellular matrix (ECM) components changes cytoskeletal organization by the activation of Rho family GTPases. Tenascin-C, a developmentally regulated matrix protein, modulates cellular responses to other matrix proteins, such as fibronectin (FN). Here, we report that tenascin-C markedly altered cell phenotype on a three-dimensional fibrin matrix containing FN, resulting in suppression of actin stress fibers and induction of actin-rich filopodia. This distinct morphology was associated with complete suppression of the activation of RhoA, a small GTPase that induces actin stress fiber formation. Enforced activation of RhoA circumvented the effects of tenascin. Effects of active Rho were reversed by a Rho inhibitor C3 transferase. Suppression of GTPase activation allows tenascin-C expression to act as a regulatory switch to reverse the effects of adhesive proteins on Rho function. This represents a novel paradigm for the regulation of cytoskeletal organization by ECM.